Alpinetin: A Review of Its Pharmacology and Pharmacokinetics - Zhao, Ge; Tong, Yue; Luan, Fei; Zhu, Wenjing; Zhan, Chenglin; Qin, Tiantian; An, Weixiao; Zeng, Nan (Frontiers in Pharmacology, 2022)
Flavonoids isolated from medicinal herbs have been utilized as valuable health-care agents due to their virous biological applications. Alpinetin is a natural flavonoid that emerges in many widely used medicinal plants, and has been frequently applied in Chinese patent drugs. Accumulated evidence has demonstrated that alpinetin possesses a broad range of pharmacological activities such as antitumor, antiinflammation, hepatoprotective, cardiovascular protective, lung protective, antibacterial, antiviral, neuroprotective, and other properties through regulating multiple signaling pathways with low systemic toxicity. However, pharmacokinetic studies have documented that alpinetin may have poor oral bioavailability correlated to its extensive glucuronidation. Currently, the reported pharmacological properties and pharmacokinetics profiles of alpinetin are rare to be scientifically reviewed. In this article, we aimed to highlight the mechanisms of action of alpinetin in various diseases to strongly support its curative potentials for prospective clinical applications. We also summarized the pharmacokinetics properties and proposed some viable strategies to convey an appreciable reference for future advances of alpinetin in drug development.